2020
DOI: 10.1155/2020/3232950
|View full text |Cite
|
Sign up to set email alerts
|

Combination Use of Tegafur and Apatinib as First-Line Therapy in Treatment of Advanced Gastric Cancer: A Single-Blinded Randomized Study

Abstract: Objective. To investigate the efficacy and safety of the combination use of tegafur and apatinib as a first-line therapy strategy in advanced gastric cancer (GC). Methods. The present study included a total of 62 advanced GC patients. The patients were randomized into the combined group (treated with both tegafur and apatinib) and the control group (treated with only tegafur). Treatment efficacy, KPS score, nutrition condition, and progression-free survival time (PFS) were recorded. Results. Both the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…One study was excluded because it could not be incorporated into network calculation 17 . Another study was excluded as the chemotherapy regimens did not meet the criteria for the standard first-line chemotherapy in NCCN 2021 guidelines 18 . Two other studies were not included because patients had previously received systemic chemotherapy within 6 months or the time of administration was not clearly indicated 19 , 20 .…”
Section: Resultsmentioning
confidence: 99%
“…One study was excluded because it could not be incorporated into network calculation 17 . Another study was excluded as the chemotherapy regimens did not meet the criteria for the standard first-line chemotherapy in NCCN 2021 guidelines 18 . Two other studies were not included because patients had previously received systemic chemotherapy within 6 months or the time of administration was not clearly indicated 19 , 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Combination therapy with apatinib, especially with paclitaxel, may confer a better survival benefit in the first-line treatment ( 132 ). However, some studies have also suggested that while increasing the curative effect, combined drug use reduced the quality of life of patients and increased the risk of adverse reactions ( 109 ).…”
Section: Tyrosine Kinase Inhibitors Currently Used To Treat Gastric C...mentioning
confidence: 99%